Dialogic communication with volunteers at Rocky Mountain National Park: a case study - Tank, Reghan S. (Kansas State University, 2019)
This report uses a theoretical basis, dialogic communication theory, for analyzing Rocky Mountain National Park’s relationship building efforts through public relations. In particular, this report analyzes how the park communicates dialogically with its internal volunteer public by utilizing a case study approach. Practical recommendations are posed for the park’s volunteer supervisors, as well as theoretical implications related to dialogic communication and volunteer communication. Suggestions for future research and report limitations are also discussed.
Keywords: Volunteer; Dialogic communication; Public relations; National park